Monocyte iron load correlates with immune suppression and sepsis severity: A longitudinal analysis - Mertens, Christina; Reuter, Diana; Ruban Agarvas, Anand; Schenz, Judith; Winkelhausen, Bastian; Hafner, Anna; Kahlert, Christoph; Dietrich, Maximilian; Fiedler-Kalenka, Mascha; Weigand, Markus A.; Muckenthaler, Martina; Fischer, Dania (Journal of infection, 2025)
Background - Sepsis is a life-threatening condition caused by a dysregulated immune response to infection. In critically ill patients, iron biomarkers are closely linked to outcomes; yet the mechanistic role of iron metabolism in sepsis progression remains unclear. - Method - To address this knowledge gap, we conducted a longitudinal clinical study in 20 sepsis patients, tracking plasma iron biomarkers together with monocyte function and iron content over five consecutive days following sepsis onset. Some patients required red blood cell transfusions during the study period. - Results - We show that anemia of inflammation is an early and prominent feature of sepsis hallmarked by iron sequestration in blood monocytes, reduced plasma iron levels and anemia. Importantly, increased iron levels in monocytes are detected already at day one following the sepsis diagnosis and the degree of iron accumulation directly correlates with sepsis severity. High monocytic iron levels further correlate with decreased human leukocyte antigen DR (HLA-DR) expression on day one, suggestive of monocyte immunosuppression. Furthermore, in iron-loaded septic monocytes mRNA levels of the non-transferrin bound iron (NTBI) transporter ZRT/IRT-like Protein 8 were significantly increased, suggesting enhanced uptake of non-transferrin bound iron that may arise from hemolysis. Interestingly, we also show that the total iron binding capacity is an important predictor of sepsis mortality, while transfusions did not correlate with an altered iron and/or inflammatory status. - Conclusions - The study highlights that early iron accumulation in monocytes is a hallmark of sepsis and is closely linked to disease severity and progression. We expect that improved insights into iron metabolism in sepsis patients may pave the way to improving therapeutic options that balance iron levels and their effects on organ functions in the future.
Online veröffentlicht: 15. November 2025, Artikelversion: 24. November 2025
Gesehen am 11.02.2026